Sistem Informasi Geografis Tempat Penampungan Sampah - Harun Musa; Rahmayanti (Universitas Negeri Gorontalo, 2021)
Garbage collection locations scattered at various points often make it difficult for citizens to find the nearest garbage collection location. Therefore, it is necessary to provide media that could help the public in finding the nearest garbage collection location. This study aims to design a geographic information system of garbage collection locations in the Pohuwato Regency area. This system will utilize tools that could be accessed for free, namely Google Maps so that the locals readily access the information needed. The method used in this research was a descriptive method. The results showed that people in Pohuwato Regency could find garbage collection locations in each sub-district which was detected through the geographic information system and thus made it easier for people to find the nearest garbage collection point.